2015
DOI: 10.1080/21645515.2015.1011572
|View full text |Cite
|
Sign up to set email alerts
|

Rickettsia rickettsiiouter membrane protein YbgF induces protective immunity in C3H/HeN mice

Abstract: Rickettsia rickettsii is the etiological agent of Rocky Mountain spotted fever (RMSF). YbgF and TolC are outer membrane-associated proteins of R. rickettsii that play important roles in its interaction with host cells. We investigated the immunogenicity of YbgF and TolC for protection against RMSF. We immunized C3H/HeN mice with recombinant R. rickettsii YbgF (rYbgF) or TolC (rTolC). Rickettsial burden and impairment in the lungs, spleens, and livers of rYbgFimmunized mice were significantly lower than in rTol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 34 publications
(36 reference statements)
0
35
0
2
Order By: Relevance
“…Class I or Class II major histocompatibility complex molecules bridge the gap between innate immunity and adaptive immunity by presenting M. tuberculosis antigens to CD4 + T cells such as 1 and 17 cells, or CD8 + T cells [164,165]. A growing number of studies have suggested that 1 and 17 cells play a central role in host protection by secreting IFN-γ, TNF-α, and IL-17 [4,[166][167][168][169][170][171][172]. However, disappointingly, some vaccines have good immune protection and safety in animal models, but unexpected safety issues still arise in clinical trials.…”
Section: Interactions Between the Host And M Tuberculosis Are Stillmentioning
confidence: 99%
“…Class I or Class II major histocompatibility complex molecules bridge the gap between innate immunity and adaptive immunity by presenting M. tuberculosis antigens to CD4 + T cells such as 1 and 17 cells, or CD8 + T cells [164,165]. A growing number of studies have suggested that 1 and 17 cells play a central role in host protection by secreting IFN-γ, TNF-α, and IL-17 [4,[166][167][168][169][170][171][172]. However, disappointingly, some vaccines have good immune protection and safety in animal models, but unexpected safety issues still arise in clinical trials.…”
Section: Interactions Between the Host And M Tuberculosis Are Stillmentioning
confidence: 99%
“…The results indicated that pNMB0315 provided exceptional immunogenicity and that the CpG adjuvant aided pNMB0315 in eliciting the production of antibodies in mice. It has been reported previously that the subclasses of IgG present in the serum may reflect the type of immune response, and that IgG2a was predominant in cellular immunity and IgG1 was predominant in humoral immunity (23). The Th1-type cytokine IFN-γ positively correlates with cell-mediated immune responses, which promote the production of IgG2a, whereas the Th2-type cytokine IL-4 is correlated with humoral immune response and promotes the production of IgG1 (24).…”
Section: Discussionmentioning
confidence: 89%
“…28,29 Ha et al 5 had previously documented specific immunity against two membrane antigens, 56-kDa typespecific antigen (TSA56) and surface cell antigen A (ScaA). Also, the cytotoxic T cells generated would destroy the infected cells through MHC class-I presentation of outer membrane-derived peptide epitopes.…”
Section: Discussionmentioning
confidence: 99%